The Hepatoprotective Role of Thiol Reductants against Mitoxantrone-Induced Liver Injury - Hossein Niknahad; Helia Hosseini; Fatemeh Gozashtegan; Farzaneh Ebrahimi; Negar Azarpira; Narges Abdoli; Reza Heidari (Shiraz University of Medical Sciences, 2017)
Mitoxantrone is anthracycline antibiotic highly effective against various human cancers. Hepatotoxicity is associated with mitoxantrone administration. On the other hand, there is no effective therapeutic option against chemotherapy-induced liver injury. The current investigation was designed to evaluate the effect of thiol reductants on mitoxantrone-induced liver injury in two experimental models. As an ex vivo model, isolated rat liver was exposed to increasing concentrations of mitoxantrone (100, 250, 750, and 1000 µM) alone or in combination with thiol-reductants (Dithiothreitol; DTT, and N-acetyl cysteine; NAC). In addition, rats (in vivo) received mitoxantrone (2.5 mg/kg, i.p, at days 1, 10, and 20), NAC (100 and 300 mg/kg/day, i.p, for 20 consecutive days) and DTT (15 and 30 mg/kg/day, i.p, for 20 consecutive days), then liver and serum pathological changes were monitored. Mitoxantrone-induced liver injury was evident in both ex vivo and in vivo experiments as assessed by pathological changes in biomarkers of liver injury, along with tissue histopathological changes. Furthermore, an increase in liver tissue markers of oxidative stress was detected in the mitoxantrone-treated group. It was found that thiol reductants significantly mitigated mitoxantrone hepatotoxicity. The data indicate that thiol reductants might serve as hepatoprotective agents against chemotherapy-induced liver injury.